Scorching chilies - Ab. Karim, Muhammad Shahrim; Ab Halim, Norhasmilaalisa (University Putra Malaysia, 2012)
Without chilies, one’s cooking would be very bland and tasteless. A dash of chilli powder will add more body and flavour to the food. Chilies are not only used in main dishes, but also in desserts, chocolates and beverages. Chillies are used for different purposes: the Malays use dried or fresh chilies by blending or pounding them using a mortar and pestle. The Indians on the other hand use green chillies and chilli powder to be added to their curries. Whereas, the Chinese only use a small amount of chillies in their cuisine. A burning hot chilly produce an awakening affect and increase the acuity of the senses. Chilies are also known for its stimulant effect; as such they help in blood circulation and raise body temperature.